Pneumomediastinum as a Manifestation of Granulomatosis with Polyangiitis - Ahmed Alhazmi; Mohamed Moulaye Cheikh; Rola Yousef Hassan (Case Reports in Rheumatology)
A 38-year-old hypertensive male with a smoking history presented to the emergency room with significant hemoptysis, arthritis, and a purpuric rash. Other findings included a dropping hemoglobin and acute kidney injury with microscopic hematuria. The pulmonary computed tomography was significant for alveolar hemorrhage and a rarely reported pneumomediastinum. Along with this constellation of findings, a positive antiproteinase 3 helped to confirm this patient’s diagnosis of granulomatosis with polyangiitis. Treatment commenced with sessions of plasma exchange and pulse steroids along with cyclophosphamide infusions. The patient had since improved and made a full recovery. This case report highlights the rarely described pneumomediastinum in association with vasculitides.